2015
DOI: 10.1126/scitranslmed.aab1482
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the alternative complement pathway preserves photoreceptors after retinal injury

Abstract: Degeneration of photoreceptors is a primary cause of vision loss worldwide, making the underlying mechanisms surrounding photoreceptor cell death critical to developing new treatment strategies. Retinal detachment, characterized by the separation of photoreceptors from the underlying retinal pigment epithelium, is a sight-threatening event that can happen in a number of retinal diseases. The detached photoreceptors undergo apoptosis and programmed necrosis. Given that photoreceptors are nondividing cells, thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 59 publications
(98 reference statements)
1
42
0
1
Order By: Relevance
“…With this in mind, our anti-CFD data indicate that photoreceptors are sensitive to C3 deposition/opsonization whereas the RPE may be more sensitive to the effects of amplifying the AP. Indeed, others have shown that complement regulators Cd55/ Cd59 are reduced specifically in the photoreceptors in a model of retinal detachment, making photoreceptors especially sensitive to opsonization and complement-mediated death (Sweigard et al, 2015). By contrast, the fact that TLR2 deficiency protected both photoreceptor numbers and the RPE implies that, in response to oxidative stress, TLR2 signaling promotes both C3 opsonization and the amplification of the AP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With this in mind, our anti-CFD data indicate that photoreceptors are sensitive to C3 deposition/opsonization whereas the RPE may be more sensitive to the effects of amplifying the AP. Indeed, others have shown that complement regulators Cd55/ Cd59 are reduced specifically in the photoreceptors in a model of retinal detachment, making photoreceptors especially sensitive to opsonization and complement-mediated death (Sweigard et al, 2015). By contrast, the fact that TLR2 deficiency protected both photoreceptor numbers and the RPE implies that, in response to oxidative stress, TLR2 signaling promotes both C3 opsonization and the amplification of the AP.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressing C3 in the retina can promote many features of AMD (Cashman et al, 2011;Rohrer et al, 2007), while inhibiting various complement factors can protect against photoreceptor cell death in models of retinal degeneration (Sweigard et al, 2015;Rohrer et al, 2007). To define a role for TLR2 in bridging oxidative stress to complement activation and assessing its function in retinal degeneration, we utilized a well-characterized light-induced photo-oxidative stress model of retinal degeneration in which locally produced C3 is known to contribute causally to retinal degeneration (Natoli et al, 2017).…”
Section: Neutralization Of Tlr2 In a Photo-oxidative Stress Model Of mentioning
confidence: 99%
See 1 more Smart Citation
“…as malondialdehyde activate complement (18); subretinal drusen from AMD patients have complement components (16); and retinal detachment down-regulates CD59, leading to MAC deposition in the photoreceptor-RPE region (19).…”
Section: Significancementioning
confidence: 99%
“…However, corresponding to the diversity of complement-related effector functions, the net impact of complement activation on neural outcomes has been quite varied, with complement inhibition by genetic or pharmacological means producing both positive and negative outcomes depending on the context. In the majority of studies, complement activation has been associated with exacerbated neurodegeneration; genetic and/or pharmacological inhibition of complement components, such as C1q (37, 38), C3 (22,(39)(40)(41), CFB and CFD (42), have decreased retinal neurodegeneration, while genetic ablation complement components in models of Alzheimer's disease (AD) (29,43) and frontotemporal dementia (44), have decreased neural loss in the brain.…”
Section: Discussionmentioning
confidence: 99%